Degree of external restraint of wall segments in semi‐massive reinforced concrete tanks: Part II: Rectangular and cylindrical segments. (25th September 2017) - Zych, Mariusz
Abstract : This paper presents graphs and formulas serving to define the distribution of the restraint degree of wall segments in cylindrical reinforced concrete tanks. The analyses were carried out according to the same assumptions as presented in the first part of this paper. It is proved that, for certain cylindrical tanks, the restraint degree in relation to code values (EN 1992–3) is significantly lower, while for others it is significantly higher. For cylindrical walls, the dependence of the wall thickness and its radius on the restraint coefficient is shown. Special attention is given to its further potential applicability; therefore, it was crucial to consider accurately and in a universal way at the same time issues like geometrical parameters of wall segments, edge restraint conditions, and the temperature profile in a given wall cross section. A practical aspect of the analysis performed is the possibility of defining the restraint degree for cases and assumptions not included in EN 1992–3.